Influence of nutrients on aquatic vegetation and trophic status of lakes: analysis of eutrophication and mitigation - Fernando García-Ávila; Estefanía García-Pizarro; Gabriela Malla-Aguilar; Camila Sánchez-Cabrera; Manuel Cadme-Galabay; Lorgio Valdiviezo-Gonzales; Rita Cabello-Torres (Results in Engineering)
The objective of this study was to systematically assess the influence of nutrient concentrations on aquatic vegetation dynamics, water quality, and biodiversity in lake ecosystems, as well as to analyze the effects of human-induced eutrophication and explore various mitigation techniques to reduce nutrient inputs and manage excessive vegetation in lakes. The PICO methodology was used, which includes Population, Intervention, Comparison and Results. A protocol was developed to determine inclusion and exclusion criteria, followed by a bibliographic search in the Scopus database, using specific keywords. In addition, the PRISMA methodology was applied to screen abstracts, assess biases, and synthesize the evidence into tables. The vegetation types most affected by increased nutrients in lakes include Eichhornia crassipes (water hyacinth), which displaces native species and affects biodiversity; Lemna spp. (duckweed), which covers the water surface and reduces available light; Microcystis spp., which forms harmful algal blooms under high nutrient concentrations; and Myriophyllum spp., whose photosynthetic capacity, crucial for stabilizing sediments, is compromised. Phosphorus was identified as the limiting nutrient in most lakes, with nitrogen:phosphorus ratios between 10:1 and 20:1, affecting water quality and biodiversity, with approximately 67 % of the studied lakes being limited by this nutrient. In oligotrophic and mesotrophic lakes, phosphorus is the most limiting, while in eutrophic systems, nitrogen can be a limiting factor. Techniques such as runoff control through vegetation barriers and sediment traps, sustainable agricultural practices, water quality monitoring systems, and methods for managing excess vegetation, including aeration, mechanical removal, and biological controls, are used to mitigate eutrophication.